1990
DOI: 10.1159/000181797
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Alpha-Melanocyte-Stimulating Hormone during the Menstrual Cycle in Women

Abstract: α-Melanocyte-stimulating hormone (α-MSH) and adrenocorticotropin (ACTH) immunoreactivity (IR) was measured in the blood of 22 healthy women with normal ovulatory process in the early and late follicular (near to ovulation) phases and in the early luteal phase of the menstrual cycle. Plasma α-MSH IR ranged from undetectable values to 81.3 pg/ml, the highest levels being found in the late follicular phase (15.52 ± 4.16 pg/ml). In contrast, plasma ACTH IR was always detectable (range: 18.5–63.2 pg/ml), but its co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…While CRH secretion has been reported to change across the menstrual cycle displaying a CRH 31 or ACTH 45 peak, respectively, around the time of ovulation, the majority of studies did not observe a change of baseline cortisol serum 3,14,[32][33][34]36,38,40,43 , salivary 14,34,38 , and urinary 14,38 levels across the menstrual cycle. These findings support the earlier systematic review from 1994 43 showing no impact of the menstrual cycle on basal serum cortisol [46][47][48][49][50][51] and serum ACTH levels 52 . Some studies also showed no difference for the menstrual cycle on basal urinary 53 and serum 45,54 cortisol levels 55 in women with PMS.…”
Section: Sdnn Index (Ms)supporting
confidence: 90%
See 1 more Smart Citation
“…While CRH secretion has been reported to change across the menstrual cycle displaying a CRH 31 or ACTH 45 peak, respectively, around the time of ovulation, the majority of studies did not observe a change of baseline cortisol serum 3,14,[32][33][34]36,38,40,43 , salivary 14,34,38 , and urinary 14,38 levels across the menstrual cycle. These findings support the earlier systematic review from 1994 43 showing no impact of the menstrual cycle on basal serum cortisol [46][47][48][49][50][51] and serum ACTH levels 52 . Some studies also showed no difference for the menstrual cycle on basal urinary 53 and serum 45,54 cortisol levels 55 in women with PMS.…”
Section: Sdnn Index (Ms)supporting
confidence: 90%
“…Most studies did not observe an impact of endogenous P exposure on baseline 14,[32][33][34]36,38,40,43,[46][47][48][49][50][51][52][53]55 or stimulated 14,30,35,41,43,44,53,56,57 HPAA. However, few studies reported higher baseline 33,37,38 and stimulated 28,36,39 cortisol levels during the follicular phase, or vice versa 3,29,39,45,54 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the studies of late 1970s, detectable levels of a-MSH plasma have been found in healthy adult volunteers (6,7), and they have been found higher than normal in patients affected by Cushing disease (8). The results of the abovementioned studies were obtained coupling the classical a-MSH RIA to purification procedures, such as extraction and HPLC, and revealed that the des-acetylated form of a-MSH (i.e.…”
mentioning
confidence: 95%